2020
DOI: 10.1039/d0cc03240a
|View full text |Cite
|
Sign up to set email alerts
|

LMCT transition-based red-light photochemotherapy using a tumour-selective ferrocenyl iron(iii) coumarin conjugate

Abstract: A mitochondria-targeted ferrocenyl iron(iii) coumarin complex shows red-light toxicity against cancer cells but remains harmless in the dark and to normal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…For the free esculetin molecule (H 2 esc), the corresponding absorption occurs at ∼347 nm. It follows that a bathochromic shift of this ligand-centered band is observed upon coordination to cobalt­(III). , The d 6 low-spin (t 2g 6 ) complexes also displayed a ligand-field d–d band in the range 650–800 nm originating from the 1 A 1g → 1 T 2g and 1 A 1g → 1 T 1g transitions (Figure S28). For complexes 3 and 6 , while the longer-wavelength regions for the d–d transitions could be seen in the spectra, the shorter-wavelength regions were masked by the appearance of the high-intensity ligand-based transitions of the coordinated dppz bases.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…For the free esculetin molecule (H 2 esc), the corresponding absorption occurs at ∼347 nm. It follows that a bathochromic shift of this ligand-centered band is observed upon coordination to cobalt­(III). , The d 6 low-spin (t 2g 6 ) complexes also displayed a ligand-field d–d band in the range 650–800 nm originating from the 1 A 1g → 1 T 2g and 1 A 1g → 1 T 1g transitions (Figure S28). For complexes 3 and 6 , while the longer-wavelength regions for the d–d transitions could be seen in the spectra, the shorter-wavelength regions were masked by the appearance of the high-intensity ligand-based transitions of the coordinated dppz bases.…”
Section: Resultsmentioning
confidence: 88%
“…The UV–visible spectra of complexes 1 – 6 measured in DMF/PBS [1:9 (v/v), pH = 7.2] displayed a common absorption band at ∼275 nm attributable to a π → π* transition (Figures a and S27). , A common band at ∼345 nm due to the n → π* transition involving the quinoxaline moiety was observed for the dipyridoquinoxaline (dpq) complexes 2 and 5 . , For the dipyridophenazine (dppz) complexes 3 and 6 , two additional absorption bands at 361 and 377 nm were observed that can be attributed to the n → π* transitions of the phenazine moiety. , Furthermore, complexes 4 – 6 showed an esculetin-based π → π* visible absorption band at ∼402 nm . For the free esculetin molecule (H 2 esc), the corresponding absorption occurs at ∼347 nm.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is the case of the in vivo photolysis of the microtubule inhibitor 4-pyridinomethylcoumarin ( Figure 8 , compound XLVIII ) [ 72 ]. 7-Hydroxymethyl substituted aminocoumarins are used as iron complexes ( Figure 8 , general structures XLIX and L ), and can be used to photochemotherapeutically target the mitochondria in the treatment of cancer [ 60 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…[33] However, ferrocenium [35,36] as a delocalized lipophilic cation has been rarely explored. [37,38] To the best of our knowledge, there are no reports about cancer-mitochondria dual-targeting platforms using carbohydrates and ferrocenium so far.…”
Section: Introductionmentioning
confidence: 99%